Early detection of lung cancer - Lam, Stephen (Henry Stewart Talks, 2009)
Lung cancer is the most common cause of cancer death world-wide, Detecting and treating the disease early is the most promising approach to improve the outcome of patients with lung cancer, Strengths and limitations of current early detection technologies, Lung cancer risk prediction models to select individuals at high risk for lung cancer